Competence-oriented vocational education and training : Approaches and Experiences in Europe - Weber, Heiko [Verfasser]; Geldermann, Brigitta [Verfasser]; Löffler, Roland [Verfasser]; Bednarz, Furio [Verfasser] (Forschungsinstitut Betriebliche Bildung, 2015)
"This volume is a product of the project “TrainCom: Developing Training Competence in IVET by Using Units of learning outcomes" (DE/13/LLP-LdV/TOI/147605) within the Lifelong Learning Programme (LLP) of the European Union. Duration of the project: 01.10.2013 until 30.09.2015. The project has been funded with support from the European Commission." (excerpt; BIBB-Doku)
Keywords: Berufsausbildung; Kompetenzorientierung; Duales System; Arbeitsmarkt; Arbeitslosigkeit